DOP07 Targeting the canonical WNT signalling pathway as a potential novel therapy in Crohn′s associated fibrosis. (30th January 2023) - Buck, A; Weber, M C; Friess, H; Neumann, P A
Abstract: Background: Crohn's disease (CD) is characterized by chronic recurrent intestinal inflammation that leads to progressive fibrotic remodelling of the intestinal wall. Despite advances in medical therapy for CD, 50% of patients still require surgical treatment after 10 years of disease mainly due to fibrosis-associated intestinal stenosis formation. A specific anti-fibrotic therapy does not yet exist, underlining the medical need for further research in this area. The exact mechanism of fibrosis development in CD fibrosis is not yet understood, but WNT signalling has been shown to play a critical role in fibrosis in other organs. However, the role of WNT-signalling in intestinal fibrosis and its potential druggability is not well characterized. Methods: Bulk RNA sequencing was performed to uncover important mechanistic pathways participating in fibrosis development in surgical specimens from patients with fibrostenosing CD. Non fibrotic non-inflamed areas of the same patients served as controls. To elucidate the functional role of matrix producing fibroblasts, primary cells were isolated from both areas. Their fibrotic potential was further characterized by flow cytometry, immunofluorescence, and RNA sequencing. Protein levels of fibrosis markers as well as WNT target genes were assessed using immunofluorescence imaging techniques. Results: Gene set enrichment (GAGE) revealed highly upregulated WNT-pathway (p adj < 0.0029) in CD fibrosis compared to matched normal tissue. Flow cytometry revealed an increased population of PDPN+, PDGFRa+ mesenchymal cells in fibrotic segments compared to non-fibrotic tissue. These cells preserve their fibrotic phenotype in vitro showing elevated expression of aSMA and COL1 in FACS. Functional and gene analysis showed upregulated migratory potential of fibrotic fibroblasts, as well as matrix production capabilities (VIM, COL1A1, FN1). RNA sequencing of tissue as well as fibroblasts revealed markedly elevated expression the Wnt1 effector WISP1, which is upregulated in fibrotic cells and tissue. In turn, WISP1 treatment of primary fibroblasts led to activation of the canonical WNT pathway, its target transcription factors and genes (LEF1, MMP7). Conclusion: Fibrosis formation in CD patients is associated with activated WNT signalling. One druggable protein, a downstream target gene of WNT-signalling could be WISP1. This will be further investigated in our in vitro as well as in our in vivo model, to propose a novel therapy for reducing surgical intervention in CD patients.